Key technical components for air pistol shooting performance - Olsson, E.; Laaksonen, M. S. (International Journal of Performance Analysis in Sport, 2021)
Air pistol shooting is a complex sport discipline with high demands on fine motor control and postural stability. Earlier studies have reported questionable results regarding the most important technical components for air pistol shooting. Therefore, the aims of the present study were to investigate the key technical components for air pistol shooting and also to investigate how well the key technical components explain the performance in air pistol shooting. Eighteen national-level air pistol shooters completed a simulated qualifying round consisting of 60 shots. During each shot, shooting score and 17 aiming point trajectory variables were measured with an optoelectronic training device. Principal component analysis revealed five key technical components: aiming time, stability of hold, aiming accuracy, cleanness of triggering and timing of triggering. Four of the five components (not aiming time) correlated significantly (r = .48 - .74; p < 0.05) with shooting score. Two stepwise multiple regression analyses identified aiming accuracy followed by timing of triggering and stability of hold as the most important components, accounting for 75-78% of the variance in shooting score. Accordingly, these components should be in focus by coaches and athletes when conducting tests and training.